The Influence of Children's Literature on Character Education with an Ethnopedology Approach for Grade VI Students Elementary School - Herlina Payuk Allo; Rita Tanduk; Dina Gasong (Universitas Islam Negeri Palopo, 2025)
This study explores the influence of children's literature—particularly Torajan folklore—on character education through an ethnopedagogic approach at SDN 3 Rantepao. Using a qualitative case study method, the research investigates how traditional stories such as Polopadang can foster core character values including honesty, hard work, gratitude, and cultural respect among sixth-grade students. Data were collected through interviews, classroom observations, documentation, and student questionnaires. The findings reveal that integrating local culture into learning activities significantly enhances students’ moral development and cultural identity. For example, students' understanding of honesty increased from 16% to 100%, and observable behaviors such as admitting mistakes and completing assignments honestly also improved. The ethnopedagogic approach proved effective in contextualizing moral values within the students' cultural environment, making character education more meaningful and impactful. This study affirms the importance of utilizing local wisdom in education to build character and preserve traditional heritage in the face of modern challenges.